The Synergy of Artificial Intelligence and Experiential Learning in Cultivating Student Creativity - Efrita Norman; Arman Paramansyah; Robiatul Adawiyah; Lina Marliani; Sofyan Mustoip (Kolej PERMATA Insan, 2025)
International Conference And Innovation On Education, Science & Technology (ICIEST 2025) “Fostering Innovation And Creativity Through Education, Science & Technology” 21st June 2025 Editor : Hatika Kaco, Diani Mardiana Mat Zin, Fadzidah Mohd Idris, Siti Munirah Mohd ,Nurhidaya Mohamad Jan, Nor Atirah Izzah Zulkefli, Nadiah Suboh Organised by : Education & Advanced Sustainability (EdAS) unit, Kolej PERMATA Insan, Universiti Sains Islam Malaysia